PIDANA KERJA SOSIAL DAN RESTITUSI SEBAGAI ALTERNATIF PIDANA PENJARA DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - Iskandar Wibawa (Jurnal Media Hukum, 2017)
Imprisonment is the criminal delict who always threatened on every offences crime althought criticized  various circles due to ineffectiveness realize the purpose of punisment, namely the social defence and fostering offender. This led to the emergence of anternatives on imprisonment in the hope purpose of punishment can be realized. The Tokyo Rules is set to 14 Desember 1990 recommending the counties in the world in order to enter the alternatives of imprisonment in a code penal include a community service order and restitution. A community service order is intended to make offenders be chastened and shammed so as not to repeat the crime (offender oriented), while restitution in the form of payments for losses incurred due to the act the offender to the victim, as an expression of remorse is expected to eliminate the conflict between the offender and the victim (victim oriented). Thus, the purposee of punishment is expected to be realized.